Effects of Aquaculture on Migration and Movement Patterns of Double-Crested Cormorants - D. Tommy King; Bradley F. Blackwell; Brian S. Dorr; Jerrold L. Belant (Human-Wildlife Interactions, 2017)
We analyzed 10,620 recovery records for double-crested cormorants (Phalacrocorax auritus) banded as nestlings from 1923 to 2006 to determine the population’s age structure, migration routes, dispersal patterns, and the possible influence of the expansion of the aquaculture industry in the southeastern United States on these population characteristics. Ninety-nine percent of the birds were banded during June to August, and 78% were banded as pre-fledged birds. Cormorants banded in the interior region of the United States comprised 91% of all birds banded from 1955 to 2006; these birds wintered primarily in the Lower Mississippi Valley and the northern Gulf of Mexico area. From 1986 to 2006, the number of bands recovered in principal aquaculture areas in the southeastern United States increased 454%, while the number of bands recovered in other areas increased 55%. Further, pre-aquaculture expansion (1923– 1985) birds were recovered at greater distances from their banding colonies than were postaquaculture expansion (1986–2006) birds. These data indicate that the expansion of southeastern aquaculture has influenced double-crested cormorant movements and migration patterns.